Environmental hazard assessment and metal contamination in coastal sediments - Ayyamperumal, Ramamoorthy; Kumari, Kajal; Gandhi, M Suresh; Huang, Xiaozhong; Chengjun, Zhang; Nazir, Nusrat; Li, Fengjie; Das, Priyanko (Chemosphere (Oxford), 2023)
In order to reduce contamination levels from diverse sources, it is important to understand the factors affecting the natural ecosystems that are impacted by coastal and marine pollution. In this study, we used GIS and remote sensing techniques to investigate and evaluate the distribution of heavy metals (Fe, Mn, Zn, Cr, Pb, Co, and Cu) in surface sediments along Tamil Nadu's East Coast (from Besant Nagar to Sathurangapattinam). The CF and Igeo of metals indicate that sediments contain no evidence of Fe, Mn, or Zn metal pollution in the sediments, with only mild contamination from Co, Cu, and Pb. In contrast, the sediment samples were found to be significantly contaminated with Cr. Heavy metal contamination occurs in the following order, according to our research: Cr > Pb > Cu > Co > Mn > Zn > Fe. Except for sites 8, 10, 11, and 13, where PLI>1 implies that there is no pollution in this area, the PLI values show that most of the locations are contaminated. The ecological risk index (ERI) values for five metals in the study areas are as follows: Cr > Pb > Cu > Mn > Zn. The sediment samples fall into the low-risk and highly polluted to dangerous sediment categories for SPI, according to the Risk index (RI). Based on the Mean Effect Range-Median Quotient (M-ERM-Q), Cu, Pb, Zn, and Cr metals in the research region have a 9–21% probability of being harmful. Statistical approaches show that the majority of heavy metals in sediments are of natural origin. The spatial distribution of heavy metals in surface sediments provides the conceptual framework for practical strategies to protect coastal areas. Many shreds of evidence indicate that anthropogenic inputs from the surrounding land area are primarily responsible for the deposition of these heavy metals in the coastal zone. [Display omitted]